Description of unknown or poorly known pupae and adult males of Neotropical Heteromyia Say (Culicomorpha: Ceratopogonidae), with a specific key to pupae - Ronderos, María Marcela (2016)
The pupae of four Neotropical species of Heteromyia Say, H. clavata Williston, H. chaquensis Duret and Lane, H. correntina Duret and Lane and H. orellana (Roback) are described, photographed and illustrated using dissecting and compound microscope Nikon Eclipse E200, and a key is presented for their identification. The adult male genitalia of H. chaquensis and H. orellana are also described. Studied specimens were collected in northeastern Argentina and in the Amazon region of Brazil and Peru. Differences and similarities between the described species are noted and discussed, and phylogenetic relationships between the species here treated and between genera in the tribe Heteromyiini are analyzed.